Resilience pathways: Understanding remittance trends in post-coup Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
Remittances have emerged as an important source of income for households in post-coup Myanmar. This paper utilizes data from the second and fifth rounds of the Myanmar Household Welfare Survey (MHWS) to analyze remittance trends between January and June 2022 and the same period in 2023. This is supplemented with data from the Myanmar Migration Assessment (MMA) which was conducted with a sub-sample of MHWS households in June and July 2023.